Chronic Oral Study of Myosin Activation to Increase Contractility in Heart Failure (COSMIC-HF): a phase 2, pharmacokinetic, randomised, placebo-controlled trial. Issue 10062 (10th December 2016) - Teerlink, John R; Felker, G Michael; McMurray, John J V; Solomon, Scott D; Adams, Kirkwood F; Cleland, John G F; Ezekowitz, Justin A; Goudev, Assen; Macdonald, Peter; Metra, Marco; Mitrovic, Veselin; Ponikowski, Piotr; et al.
Summary: Background: Impaired contractility is a feature of heart failure with reduced ejection fraction. We assessed the pharmacokinetics and effects on cardiac function and structure of the cardiac myosin activator, omecamtiv mecarbil. Methods: In this randomised, double-blind study, done at 87 sites in 13 countries, we recruited patients with stable, symptomatic chronic heart failure and left ventricular ejection fraction 40% or lower. Patients were randomly assigned equally, via an interactive web response system, to receive 25 mg oral omecamtiv mecarbil twice daily (fixed-dose group), 25 mg twice daily titrated to 50 mg twice daily guided by pharmacokinetics (pharmacokinetic-titration group), or placebo for 20 weeks. We assessed the maximum concentration of omecamtiv mecarbil in plasma (primary endpoint) and changes in cardiac function and ventricular diameters. This trial is registered withClinicalTrials.gov, numberNCT01786512 . Findings: From March 17, 2014, to March 5, 2015, we enrolled 150 patients in the fixed-dose omecamtiv mecarbil group and 149 in the pharmacokinetic-titration and placebo groups. Mean maximum concentration of omecamtiv mecarbil at 12 weeks was 200 (SD 71) ng/mL in the fixed-dose group and 318 (129) ng/mL in the pharmacokinetic-titration group. For the pharmacokinetic-titration group versus placebo group at 20 weeks, least square mean differences were as follows: systolic ejection time 25 ms (95% CI 18–32, p<0·0001), stroke volume 3·6 mL (0·5–6·7, p=0·0217), left ventricular end-systolic diameter −1·8 mm (−2·9 to −0·6, p=0·0027), left ventricular end-diastolic diameter −1·3 mm, (−2·3 to 0·3, p=0·0128), heart rate −3·0 beats per min (−5·1 to −0·8, p=0·0070), and N-terminal pro B-type natriuretic peptide concentration in plasma −970 pg/mL (−1672 to −268, p=0·0069). The frequency of adverse clinical events did not differ between groups. Interpretation: Omecamtiv mecarbil dosing guided by pharmacokinetics achieved plasma concentrations associated with improved cardiac function and decreased ventricular diameter. Funding: Amgen.